2004
DOI: 10.1097/00043426-200401000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to Treatment for Extraocular Retinoblastoma

Abstract: Extraocular retinoblastoma is associated with a very poor outcome. At Children's Hospital Los Angeles, 10 of 207 patients with retinoblastoma had extraocular disease. Four patients with no histopathologic risk factors developed extraocular disease. All patients with direct extension into the central nervous system or with distant metastatic disease died. One of three patients with trilateral retinoblastoma and one patient with regional recurrence are alive after autologous bone marrow transplant. Patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
57
1
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 8 publications
4
57
1
6
Order By: Relevance
“…This trend can be due to poverty, low socio-economic status, illiteracy, lack of access to tertiary oncology centres thus causing a delay in presentation and, consequently a delay in diagnosis and subsequent treatment. Also a greater number of cases with extra-ocular extension and metastasis are seen in developing countries as compared to developed nations where the incidence is only 2% to 5% (7).…”
Section: Discussionmentioning
confidence: 99%
“…This trend can be due to poverty, low socio-economic status, illiteracy, lack of access to tertiary oncology centres thus causing a delay in presentation and, consequently a delay in diagnosis and subsequent treatment. Also a greater number of cases with extra-ocular extension and metastasis are seen in developing countries as compared to developed nations where the incidence is only 2% to 5% (7).…”
Section: Discussionmentioning
confidence: 99%
“…5,14,[16][17][18][19][20] To our knowledge, only two reports included more than 10 patients and they concluded that consolidation with HDC and ASCR provides a chance for cure, estimated to be in the range of 60-70%, especially for children with metastatic disease outside the CNS. 6,15 Despite the fact the results in children with CNS dissemination were poorer, recent reports showed that some children with CNS invasion 14 or with trilateral disease 21 could be cured with this strategy.…”
Section: Discussionmentioning
confidence: 99%
“…These include: the proposed superiority of thiotepacontaining regimens and the use of post transplant radiotherapy to involved bulky sites that could not be addressed by this study and the previous reports. 5,6,[16][17][18]20,26 The current international multi-center trial (COG ARET 0321) will be a key instrument for responding these questions. 27 Metastatic retinoblastoma is now less frequent in South America, 28 probably because of earlier diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The overall occurrence of extraocular retinoblastoma was 4.8% of all patients at an institution. 3 Since retinoblastoma is highly chemosensitive, a treatment strategy that includes the dose-escalation of chemotherapeutic agents and stem cell support should be promising. We treated five patients with metastatic retinoblastoma using high-dose chemotherapy (HDC) followed by autologous stem cell transplantation (SCT), and three patients are currently alive and disease-free.…”
mentioning
confidence: 99%